2022
DOI: 10.3389/fonc.2022.833775
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Recurrence of Papillary Thyroid Carcinoma in Children and Adolescents

Abstract: BackgroundThe incidence of papillary thyroid carcinoma (PTC) in children and adolescents has increased, but the data on long-term outcomes are limited. There are few literatures on the clinicopathological characteristics and prognosis of PTC in children and adolescents in China. Therefore, it is necessary to identify clinicopathological features to precisely predict clinical prognosis and to help choose the optimal method and perform the best therapeutic regimen.MethodsThis study was a retrospective analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 29 publications
3
13
0
2
Order By: Relevance
“…PTC in children and adolescents is less common, but the recurrence rate is high (16.7-31.6%) ( 30 32 ). The results of our study showed that 40 patients (22.3%) had a recurrence, which was similar to Rubinstein’s study ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…PTC in children and adolescents is less common, but the recurrence rate is high (16.7-31.6%) ( 30 32 ). The results of our study showed that 40 patients (22.3%) had a recurrence, which was similar to Rubinstein’s study ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of eighteen articles dealing with thyroid surgery in paediatric population is shown in Table 3 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies (18) included in our literature review were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…Study period varied from 1 year [ 17 ] to 18 years [ 22 ]. Studies with the most patients were those in which partial or total thyroidectomy was usually performed [ 12 , 13 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], while fewer patients were included in studies that analysed robotic trans-axillary and retro-auricular approach [ 14 ] or transoral endoscopic thyroidectomy via vestibular approach [ 17 ]. The most common complication in all operations was hypocalcaemia due to incidental parathyroidectomy and recurrent laryngeal nerve injury.…”
Section: Resultsmentioning
confidence: 99%
“…Виявлено, що МФ була незалежним чинником ризику для кількості метастазів у ЦЛВ і ЛЛВ [44], а дослідження D. Q. Ngo та співавт. [82] показало, що у дітей з ПРЩЗ МФ, максимальний діаметр пухлини, ЕТП і метастази у ЦЛВ були незалежними чинниками ризику метастазування у ЛЛВ.…”
Section: значення мультифокальностіunclassified
“…У дослідженні Y. Gui та співавт. [44] показано, що вогнища раку у віковій групі < 14 років були агресивнішими та переважно МФ порівняно з групою 14 -18 років. Дослідження S. Park [92] показало, що вікова група < 15 років мала агресивніші чинники, зокрема білатеральність і МФ.…”
Section: дитячий вікunclassified